The Magic Figer - "Dahl, Roald" (puffin books: London, 2000)
Illustrated by Quentin Blake, this classic Dahl story is about an unusual little girl who has a magic finger. When things go wrong, she inflicts punishment by flashing her magic finger. The results include her teacher growing whiskers & a tail
Keywords: Hunters Juvenile fiction